LEADER-MEMBER EXCHANGE SEBAGAI PEMODERATOR DALAM PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PERSEPSI TENTANG RASA KEADILAN ORGANISASIONAL: STUDI LITERATUR - Rizka Nugraha Pratikna (Bina Ekonomi, 2015)
Every organization has leaders that supporting them to gain the goal. Leaders interact with their subordinates as organization’s most important resource. The concept of transformational leadership is creating vision and climates’ that can motivate everyone to perform more than the expectation. Transformational leadership concept has influence on the organizational justice perception with Leader-Member Exchange (LMX) as moderator. The core of justice principle delineate that employees need appreciation of human’s rights and prestige; thus, employees’ perception of organizational justice is an important thing, because it is directly related to organization’s growth. The most important thing is:every organization should evaluate leadership continuously because the improvement of subordinates’ positive perception of justice will in turn help the company’s growth. Besides, the relationship between leaders and subordinates should be maintenanced, based on leader-member exchange principle.Keywords: Transformational leadership, organizational justice, leader-member exchange (LMX).